Making Choices in Discourse: New Alternative Masculinities Opposing the “Warrior’s Rest” - Ruiz-Eugenio, Laura; Toledo del Cerro, Ana; Crowther, Jim; Merodio, Guiomar (Frontiers in Psychology, 2021)
Psychology research on men studies, attractiveness, and partner preferences has evolved from the influence of sociobiological perspectives to the role of interactions in shaping election toward sexual–affective relationships and desire toward different kinds of masculinities. However, there is a scientific gap in how language and communicative acts among women influence the kind of partner they feel attracted to and in the reproduction of relationship double standards, like the myth of the “warrior’s rest” where female attractiveness to “bad boys” is encouraged or supported. Some women imitate “the warrior” behavior of men by choosing dominant traditional masculinities (DTM) to have “fun” with and oppressed traditional masculinities (OTM) for “rest” after the “fun” with DTM—choosing an OTM for a stable relationship, but perhaps without passion, while also feeling attraction toward DTM, a response which perpetuates the chauvinist double standard that the feminist movement has condemned when men behave in this sexist way. Through conducting a qualitative study with communicative daily life stories, this article explores, on the one hand, how language and social interaction among women can lead to the reproduction of the DTM role by women and, on the other hand, also how new alternative masculinities (NAM) offer an alternative by explicitly rejecting, through the language of desire, to be the rest for the female warrior, the second fiddle to any woman. This has the potential to become a highly attractive alternative to DTM. Findings provide new knowledge through the analysis of communicative acts and masculinities evidencing the importance of language uses in the reproduction of the double standards in gender relations and to understand how and why these practices are maintained and which kind of language uses can contribute to preventing them. Implications for research and interventions on preventive socialization of gender violence are discussed.